Prevention of scale formation and saline wastewater discharge during district heating systems operation - Высоцкий, Сергей Павлович; Варивода, Алексей Витальевич (Eastern-European Journal of Enterprise Technologies, 2013)
The factors, determining the intensity of scale formation in district heating systems, were considered. For "closed" systems scale formation intensity is defined by the carbonate index, which is standardized by the rules of technical operation depending on the temperature of water heating. For "open" systems, which have direct contact with the atmosphere (circulating water cooling systems), the intensity of salts accumulation is proportional to the product of calcium hardness and square alkalinity of water. The equations were derived, which allow determining the required load by absorbed cations on weakly acidic cation exchange resins and, accordingly, the required amount of filters media. Replacing traditional technology of preparation of make-up water of heating systems using sodium cycling method by water treatment in filters, loaded by weakly acidic cation exchange resin with further decarbonization, allows reducing reagent consumption by 8 times and significant reduction of saline wastewater discharge into surface water reservoirs. The results of studying the process of softening waste regeneration solutions by soda and lime are given. Reduction of wastewater hardness to the values<3mg∙ekv/dm3 requires precise dosing of reagents.